THE EFFECTIVENESS OF ACUPUNCTURE ON ORTHOPAEDIC PAIN WITHIN A VOCATIONAL REHABILITATION SETTING - Chetty, Laran (Journal of Vocational Health Studies, 2022)
Background: Acupuncture is rapidly rising in popularity within western populations since its development and consequently there is increasing interest from a variety of clients. Purpose: To evaluate the effectiveness of acupuncture on orthopaedic pain within a vocational rehabilitation setting in London, United Kingdom. Method: A retrospective service evaluation design. A pre- and post-acupuncture questionnaire was utilised as the data collection tool. Result: Eighty-six clients were included in this evaluation because they met the criteria for inclusion. Analysis on the age differences between males and females were not statistically significant (p=0.05). The conditions that were most frequently seen at the clinic included: 57% (49/86) spinal pain; 28% (24/86) upper limb pain; and 15% (13/86) lower limb pain. The mean number of treatment sessions for acupuncture was three (range=1-6). Overall each session of treatment lasted on average twenty minutes (range=15-30). The total number of needles used during each session of treatment averaged five (range=3-8). The reported benefit of treatment was 44% (38/86) excellent, 49% (42/86) good, and 7% (6/86) poor. Conclusion: This evaluation has demonstrated that acupuncture is effective on orthopaedic pain within a vocational rehabilitation setting. Repeat audits and larger sample sizes are needed for confirmation the findings.